Antibacterial Activity of Ethanol Extract of Cocoa Leaves (Theobroma cacao L.) Against Gastrointestinal Infection Bacteria Tract Infection by Agar Diffusion Method - Sya’baniyah Herman, Nur Fajriah; Fitriana, Fitriana; Maryam, St. (Journal Microbiology Science, 2025)
The cocoa plant (Theobroma cacao L.) leaves contain secondary metabolites, including flavonoids, saponins, and tannins, known for their potential antibacterial properties. This study aims to evaluate the antibacterial activity of the ethanol extract of cocoa leaves (Theobroma cacao L.) against bacteria that cause gastrointestinal infections using the agar diffusion method. The study assessed the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the extract. The results showed that the ethanol extract exhibited significant antibacterial activity, particularly at concentrations of 2.5%, 5%, and 10%, with the highest inhibition zone observed at 10% concentration. The extract was most effective against Escherichia coli, Salmonella typhi, Shigella dysenteriae, and Vibrio cholerae, with inhibition zones of 15.34 mm, 15.60 mm, 13.81 mm, and 16.43 mm, respectively. These findings suggest that cocoa leaf extract has the potential to be developed as an antibacterial agent against gastrointestinal pathogens.